Application of a new Terrestrial Telecommunications System in the European Air Traffic - Marin, Draško; Kovač-Striko, Elizabeta (Promet - Traffic&Transportation, 2012)
Aeronautical Public Correspondence (APC) is a telecommtmicationsse!Vice, which enables passengers onboard aircraftto make telecommunication calls to people on the ground.This article describes the terrestrial communications seiVicewhich is based on cellular network for the European CEPTmember countries (CEPT- European Conference of Postaland Telecommunications Administrations) named TerrestrialFlight Telecommunications System (TFTS).This system is a Pan-European System, which means theusage of hannonised frequencies in Europe with hannonisedstandards for the TFTS equipment, which have been issued bythe European Telecommunications Standard Institute (ETSI).Frequencies allocated for TFTS have been designated bythe World Administrative Radio Conference, WARC-92 withfrequency bandwidth of 2x5 MHz:1670- 1675 MHz, for ground to air1800- 1805 MHz, for air to ground.TFTS planning is perfonned by the application of frequencyblocks (42 blocks) with 164 channels in total. Bandwidthof each radio channel, which contains 4 speech channels,is equal to 30.3 kHz.Due to the very high flight of the aircraft (about 13,000 m),it needs a long distance between the centres of cells (radio stationon the ground) to avoid the eo-channel or adjacent channelinteJference.The article presents the planning process with typical cellradius of240km or 350km. In the viewofthatfact, the need ispointed out for finding a compromise solution with regard toemitting power and the influence of interference.Final(v, it is noted that TFTS ground radio stations inCroatia, which are located in Zagreb and Split, may cover theterritory of some neighbouring countries other than Croatia,which is important from the commercial point of view.